Job Satisfaction and Turnover Intention in Organizations: A Study Across Sectors in Indian Perspective - Sowmya, K. R. (Prabandhan: Indian Journal of Management, 2013)
Several organizations are facing a serious threat of employee turnover irrespective of sectors, across countries. This study is an attempt to identify the factors influencing job satisfaction and turnover intention of employees from multiple sectors in Chennai city. The researcher considered a sample of 598 employees across various sectors to find out the varied opinions about the levels of satisfaction experienced by them. The researcher adopted non probability convenience sampling for choosing the respondents from Chennai city in South India. Exploratory factor analysis, K-Means cluster analysis, and t-test were adopted for analysis of the collected data. As a result, three clusters of people influenced by five major factors of job satisfaction were identified. A negative relationship between turnover and job satisfaction was found, which is consistent with many of the previous studies conducted in this area.